Partijraad PvdA, Meervaart Amsterdam. Rotterdamse delegatie van de partijraad. V.l.n.r.: De Vries, Henderson, Van Dijk, Koreman en Van Wijk - Sonneveldt, Ton,
Partijraad PvdA, Meervaart Amsterdam. Rotterdamse delegatie van de partijraad. V.l.n.r.: De Vries, Henderson, Van Dijk, Koreman en Van Wijk.